2021
DOI: 10.2147/jir.s311640
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Implications of Coexisting Type 2 Inflammatory Diseases

Abstract: The role of type 2 inflammation in the pathogenesis of certain human diseases is an area of active investigation. Certain asthma, atopic dermatitis, eosinophilic esophagitis, and chronic rhinosinusitis phenotypes are characterized by a Th2 predominant inflammatory pathway and are frequently associated with comorbid conditions in patients. The purpose of this article is to review the evidence behind concurrent Th2-mediated diseases and explore how the presence of these comorbid conditions affect patient and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…A recent study demonstrated the concurrent efficacy of Dupilumab in AD, asthma and chronic sinonasal conditions, however, the question of whether a unique therapy could lead to a concomitant improvement of all the aforementioned diseases still remains to be further investigated ( 2 , 33 ). Multiple data already exist showing an improvement in asthma after treatment of CRSwNP and vice versa ( 1 , 2 , 7 , 12 ), supporting the link between upper and lower airway diseases ( 5 , 36 ). In parallel, future research should establish whether biologics should be used in case of moderate CRSwNP and moderate asthma and whether use of biologics can prevent the development of other Type 2 comorbidities and similarly prevent the need for surgical interventions ( 12 ).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…A recent study demonstrated the concurrent efficacy of Dupilumab in AD, asthma and chronic sinonasal conditions, however, the question of whether a unique therapy could lead to a concomitant improvement of all the aforementioned diseases still remains to be further investigated ( 2 , 33 ). Multiple data already exist showing an improvement in asthma after treatment of CRSwNP and vice versa ( 1 , 2 , 7 , 12 ), supporting the link between upper and lower airway diseases ( 5 , 36 ). In parallel, future research should establish whether biologics should be used in case of moderate CRSwNP and moderate asthma and whether use of biologics can prevent the development of other Type 2 comorbidities and similarly prevent the need for surgical interventions ( 12 ).…”
Section: Discussionmentioning
confidence: 80%
“…Biologics are monoclonal antibodies that, in this case, target Type 2 mediators. Asthma, AD and CRSwNP are inflammatory diseases among subgroups that share common pathophysiological mechanisms which explain their frequent co-existence ( 1 , 2 ). Targeting the key drivers of Type 2 inflammation has a therapeutic effect on both AD, asthma and CRSwNP ( 12 , 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Chronicity and high impact on QoL of these conditions need a targeted and effective long-term treatment. 8 Current therapeutic approach focuses on controlling inflammation, which is characterized by massive tissue T-helper (Th)2 cell infiltration and increased levels of Th2 cytokines, mostly IL-4 and IL-13. 8 By blocking IL-4 and IL-13 overexpression, dupilumab has been demonstrated to be effective in type 2-related diseases, with few and well-tolerated AEs.…”
mentioning
confidence: 99%